Influence of Regional Financial Responsibility, Degree of Fiscal Desentralization and Level Financing Level to Allocation of Capital Government Regency / Central Java City - ., Irwanto; Hendra Titisari, K; Chomsatu, Y (KnE Social Sciences, 2018)
The purpose of his study is to examine the influence of regional financial dependence, the degree of fiscal decentralization, and the financing of SILPA on allocation capital expenditure of regency/municipal governments in Central Java period 2014-2016. While the population used by all district/municipal governments in Central Java period 2014-2016 with sampling technique using saturated sampling so that the sample used is 105 local government financial statements (LKPD). The data analysis method used is multiple linear regression analysis, with the help of SPSS 22 program. The result of the research shows that the variable of fiscal decentralization degree, and SILPA financing influence to capital expenditure allocation, while the dependent variable of finance does not affect the allocation of capital expenditure. So the independent variable capable of completing the dependent variable of 5.3%. Keywords: Allocation of Capital Expenditure, Dependency of Regional Finance, Fiscal Decentralization Degree, and Financing of SILPA.